Factors Predicting Recurrence After Resection of Clival Chordoma Using Variable Surgical Approaches and Radiation Modalities. Issue 2 (February 2015) - Jahangiri, Arman; Chin, Aaron T.; Wagner, Jeffrey R.; Kunwar, Sandeep; Ames, Christopher; Chou, Dean; Barani, Igor; Parsa, Andrew T.; McDermott, Michael W.; Benet, Arnau; El-Sayed, Ivan H.; Aghi, Manish K.
Abstract : BACKGROUND: Clival chordomas frequently recur because of their location and invasiveness. OBJECTIVE: To investigate clinical, operative, and anatomic factors associated with clival chordoma recurrence. METHODS: Retrospective review of clival chordomas treated at our center from 1993 to 2013. RESULTS: Fifty patients (56% male) with median age of 59 years (range, 8-76) were newly diagnosed with clival chordoma of mean diameter 3.3 cm (range, 1.5-6.7). Symptoms included headaches (38%), diplopia (36%), and dysphagia (14%). Procedures included transsphenoidal (n = 34), transoral (n = 4), craniotomy (n = 5), and staged approaches (n = 7). Gross total resection (GTR) rate was 52%, with 83% mean volumetric reduction, values that improved over time. While the lower third of the clivus was the least likely superoinferior zone to contain tumor (upper third = 72%/middle third = 82%/lower third = 42%), it most frequently contained residual tumor (upper third = 33%/middle third = 38%/lower third = 63%; P < .05). Symptom improvement rates were 61% (diplopia) and 53% (headache). Postoperative radiation included proton beam (n = 19), cyberknife (n = 7), intensity-modulated radiation therapy (n = 6), external beam (n = 10), and none (n = 4). At last follow-up of 47 patients, 23 (49%) remain disease-free or have stable residual tumor. Lower third of clivus progressed most after GTR (upper/mid/lower third = 32%/41%/75%). In a multivariate Cox proportional hazards model, male gender (hazard ratio [HR] = 1.2/ P = .03), subtotal resection (HR = 5.0/ P = .02), and the preoperative presence of tumor in the middle third (HR = 1.2/ P = .02) and lower third (HR = 1.8/ P = .02) of the clivus increased further growth or regrowth, while radiation modality did not. CONCLUSION: Our findings underscore long-standing support for GTR as reducing chordoma recurrence. The lower third of the clivus frequently harbored residual or recurrent tumor, despite staged approaches providing mediolateral (transcranial + endonasal) or superoinferior (endonasal + transoral) breadth. There was no benefit of proton-based over photon-based radiation, contradicting conventional presumptions. ABBREVIATIONS: GTR, gross total resection IMRT, intensity-modulated radiation therapy STR, subtotal resection UCSF, University of California, San Francisco Abstract : Supplemental Digital Content is Available in the Text.